High Attack Rate of Severe Acute Respiratory Syndrome Coronavirus 2 B.1.1.529 Among 2-Dose Vaccinated Populations in 2 Indoor Entertainment Setting Outbreaks. (7th May 2022) - Liu, Bette; Stepien, Sandrine; Pye, Victoria; Law, Charlee; Dalton, Craig; Durrheim, David N; Macartney, Kristine
Abstract: We estimated attack rates of severe acute respiratory syndrome coronavirus 2 Omicron (B.1.1.529) infection among people attending a nightclub and a graduation ball where >95% had at least 2 vaccine doses. Attack rates were 295 of 535 (55.1%) and 102 of 189 (54.0%), respectively (mean, 5 days postevent). At the ball, attack rates increased with time since vaccination: 12.5% among those vaccinated 1–2 months previously and 68.0% among those vaccinated ≥3 months previously; such differences were not found at the nightclub. Recent vaccination prevents Omicron infection, but is time and setting dependent, emphasizing the importance of nonpharmaceutical public health measures in addition to vaccine booster doses to maximize protection in high-risk contexts. Abstract : SARS-CoV-2 Omicron attack rates of >50% were found in 2 outbreaks in indoor entertainment venues among populations vaccinated with 2 doses. Our findings demonstrate the importance of nonpharmaceutical public health measures in addition to vaccination to prevent virus transmission.